2009
DOI: 10.1002/esp.1685
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial behaviour of rip channels in a multiple‐barred coastal system

Abstract: A 15-month data set of daily time-averaged video images (Argus) has been analyzed to describe the spatial and temporal variability of the rip channels on a multiple-barred coast at Noordwijk aan Zee, The Netherlands. The landward boundary of the intertidal bars and a proxy of the subtidal bar crest, defined as the intertidal and subtidal bar lines respectively, were derived from the Argus images. Local seaward-directed deviations of the bar lines represent the cross-shore and alongshore locations of the rip ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
(67 reference statements)
2
35
0
Order By: Relevance
“…Clear coupling patterns in double sandbar systems, such as in Figures 1, 8 and 9, are however rarely observed in the fi eld (Van Enckevort and Wijnberg, 1999;Castelle et al, 2007;Quartel, 2009). More often, inner-bar rip channels possess remarkably smaller and more variable alongshore scales than the outer bar (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Clear coupling patterns in double sandbar systems, such as in Figures 1, 8 and 9, are however rarely observed in the fi eld (Van Enckevort and Wijnberg, 1999;Castelle et al, 2007;Quartel, 2009). More often, inner-bar rip channels possess remarkably smaller and more variable alongshore scales than the outer bar (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…cally face outer-bar horns, a situation reminiscent of the commonly observed 180° out-of-phase relationship of inner-bar patterns and shoreline rhythms (Sonu, 1973). Quartel (2009) observed a coupling of the intertidal morphology to the subtidal alongshore variability, with the phase between the two bar variabilities varying from in-phase (0°) to out-of-phase (180°), with gradual phase changes due to different alongshore migration rates of the bars. In addition, Castelle et al (2007) noted the systematic occurrence of two inner-bar rip channels within one outer-bar crescent, revealing the existence of a possible relationship at half of the outer-bar wavelength.…”
Section: Introductionmentioning
confidence: 95%
“…Clear coupling patterns in double sandbar systems, such as those presented in Van Enckevort and Wijnberg, 1999;Castelle et al, 2007;Quartel, 2009 and Part 1), are however rarely observed in the fi eld (Hom-ma and Sonu, 1962;Goldsmith et al, 1982;Bowman and Goldsmith, 1983). More often, inner-bar rip channels possess remarkably smaller and more variable alongshore scales than the outer bar (Barusseau et al, 1994;Van Enckevort et al, 2004;Lafon et al, 2004Lafon et al, , 2005.…”
Section: Introductionmentioning
confidence: 86%
“…These techniques were used to extract datasets of up to 4 years (e.g., Holman et al, 2006); timescales that would be unfeasible to measure in-situ. A major limiting factor on the length of rip datasets that can be generated is that all attempts thus far required various degrees of manual input (Bogle et al, 2000;Gallop et al, 2009;Holman et al, 2006;Quartel, 2009;Ranasinghe et al, 1999;Turner et al, 2007;Whyte et al, 2005). The majority of research using video images uses the raw image products (snapshot, timex, daytime, etc.)…”
Section: Introductionmentioning
confidence: 99%